Furazidine (Furamag®) in the management of acute and recurrent cystitis in women - D. Yu. Pushkar; A. N. Bernikov; P. I. Rasner; A. V. Bormotin; V. V. Dyakov; A. M. Shvedov (Вестник урологии, 2025)
Cystitis is a common disease worldwide, with up to 36 million cases recorded annually in Russia alone. In 10 % of patients, the condition transforms into a chronic recurrent form. Up to 30 % of visits to outpatient urologists are related to acute or recurrent cystitis. The prevalence of chronic cystitis in women is closely linked to the anatomical and topographical characteristics of the genitourinary system, the presence of gynecological diseases, and hormonal status. Effective treatment for acute or chronic cystitis involves complex therapy, with the key to success lying in the appropriate selection of antibacterial drugs. The current study aimed to analyse the literature data on the effectiveness of Furamag® in the complex treatment of patients with acute and chronic cystitis. To achieve this objective, we conducted a search for articles in scientific databases such as PubMed, Medline, minzdrav.gov.ru, and elibrary.ru using the following keywords: «urinary tract infection», «acute cystitis», «chronic cystitis», «furazidine», «potassium furazidine». Based on the results of our search, we concluded that Furamag® has been successfully used for a long time in the treatment of both acute and chronic cystitis, demonstrating high efficacy and good patient tolerance. This explains its widespread use in routine clinical practice among urologists, gynecologists, and therapists.